2014
DOI: 10.1186/s12866-014-0313-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nested, multiplex, qPCR; FISH; SeptiFast and blood culture methods in detection and identification of bacteria and fungi in blood of patients with sepsis

Abstract: BackgroundMicrobiological diagnosis of sepsis relies primarily on blood culture data. This study compares four diagnostic methods, i.e. those developed by us: nested, multiplex, qPCR (qPCR) and FISH with commercial methods: SeptiFast (Roche) (SF) and BacT/ALERT® 3D blood culture system (bioMérieux). Blood samples were derived from adult patients with clinical symptoms of sepsis, according to SIRS criteria, hospitalized in the Intensive Care Unit.ResultsUsing qPCR, FISH, SF, and culture, microbial presence was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
(35 reference statements)
2
23
0
Order By: Relevance
“…Similar results obtained using SeptiFast test (Roche) demonstrated the presence of bacteria in 75 % of analyzed blood samples [17]. Gosiewski et al, thanks to the nested PCR method, indicated that 71.8 % of analyzed samples tested positive for bacterial presence [8]. …”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Similar results obtained using SeptiFast test (Roche) demonstrated the presence of bacteria in 75 % of analyzed blood samples [17]. Gosiewski et al, thanks to the nested PCR method, indicated that 71.8 % of analyzed samples tested positive for bacterial presence [8]. …”
Section: Discussionsupporting
confidence: 53%
“…In addition, blood culture method detects only viable bacterial cells. There are also few molecular, culture-independent methods, such as PCR or FISH (Fluorescent In Situ Hybridization), that enable the detection of selected species of bacteria based on the presence of their DNA [7, 8]. These techniques are very sensitive and allow for quick detection of even a very low number of microorganisms in the samples.…”
Section: Introductionmentioning
confidence: 99%
“…In this respect, the safety of the blood supply, as well as our understanding of the involvement of the blood microbiome in health and disease, may benefit from sensitive and exhaustive methods to detect bacteria in blood such as quantitative polymerase chain reaction (qPCR) and high‐throughput targeted metagenomics sequencing. These methods, which are already used in some cases to screen for sepsis in which a single bacterial strain is highly present in blood, are much more challenging to apply to blood from healthy donors. Not only is the blood microbiome highly diverse but, in addition, the overall bacterial quantity present in the blood of healthy individuals is obviously much lower than in the case of sepsis.…”
mentioning
confidence: 99%
“…[13] Lowest sensitivity reported was 10 1 CFU/ml for each of the four studied species of microorganisms (Escherichia coli, Staphylococcus aureus, Candida albicans and Aspergillus fumigatus). [14] This difference in LOD may be due to various factors like method of DNA extraction, primersprobes used, reagents and PCR reaction used.…”
Section: Discussionmentioning
confidence: 99%